Pengaruh Leverage dan Faktor lainnya terhadap Kesulitan Keuangan yang dimoderasi Kepemilikan Manajerial - Afifah, Hana Nur (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The aim of this research is to provide empirical evidence regarding the influence of leverage, liquidity, operating capacity, debt to asset ratio, return on asset, and gender diversity as independent variables, as well as variables moderated by managerial ownership (leverage, liquidity, and operating capacity) on financial distress. This research uses samples from all companies in the consumer cyclicals and non-cyclicals sectors listed on the Indonesia Stock Exchange (IDX) during 2019 to 2022. The sample selection used a purposive sampling method with a total of 64 companies, resulting in 256 data. The result of this research show that leverage, liquidity, operating capacity, debt to asset ratio, and gender diversity do not have a significant impact on financial distress. However, the return on asset variable has a positive effect on financial distress. Another finding is that managerial ownership cannot moderate the relationship between leverage, liquidity, and operating capacity with financial distress.